Moderately common plants show highest relative losses. Issue 1 (17th September 2019) - Jansen, Florian; Bonn, Aletta; Bowler, Diana E.; Bruelheide, Helge; Eichenberg, David
Abstract: Nature conservation efforts often focus on rare species. Common and moderately common species, however, receive much less attention. Our analysis of occupancy change of flora using a grid survey in 1980 and a habitat mapping survey in 2000 in Northeast Germany revealed significant losses for most of the 355 modeled plant species. Highest losses were recorded for moderately common species. Plant species occurring in 20–40% of grid cells declined on average by 50% in 20 years, although there were some methodological uncertainties. We found no correlation between occupancy decline and Red List category, but habitat loss seems to be a main driver. We suggest to rethink conservation indicators by including previously common species in monitoring. Our approach to estimating trends, using the association of species to habitat types and occupancy–area relationships, can be applied to other regions with heterogeneous resurvey data, but it cannot replace urgently needed monitoring schemes.